Screening for alcohol use disorder among individuals with comorbid psychiatric disorders: Diagnostic accuracy in a sample of young Swiss men. (July 2020) - Baggio, Stéphanie; Baudat, Sophie; Daeppen, Jean-Bernard; Gmel, Gerhard; Heller, Patrick; Perroud, Nader; Rothen, Stéphane; Sporkert, Frank; Studer, Joseph; Wolff, Hans; Iglesias, Katia
Highlights: High symptomatology on psychiatric disorders changed the optimal cut-off score of the AUD screening tool. AUD should be screening in conjunction with other psychiatric disorders. There is a need of an integrated approach to screening for AUD. Abstract: Alcohol use disorder (AUD) is frequently comorbid with other psychiatric disorders. However, few studies investigated the psychometric properties of AUD screening tools in presence of co-occurring disorders. This study examined the diagnostic accuracy of a short AUD screening tool among young adults, in the presence of high vs. low or moderate symptomatology of other common psychiatric disorders. Data were collected among young Swiss men ( n  = 233) between 2016 and 2018. Measures included a diagnostic interview for AUD and screening tools for AUD and other psychiatric disorders (attention deficit hyperactivity disorder, antisocial personality disorder, bipolar disorder, borderline personality disorder, major depressive disorder, and social anxiety disorder). We computed receiver operating characteristic curves to test whether the AUD screening tool was an accurate indicator of AUD for groups with high vs. low or moderate symptomatology of each psychiatric disorder. The results showed that the optimal cut-off score was ≥3 (the original cut-off of the scale) for participants with a low or moderate symptomatology and ≥4 for participants with a high symptomatology. Our findings highlighted the urgent need for an integrated approach to screening. Psychiatric comorbidities should be included in the screen for AUD to obtain accurate results.